Higher plasticity in feeding preference of a generalist than a specialist: experiments with two closely related Helicoverpa species - Wang, Yan (Sci Rep, 2017)
Herbivorous insects have been categorized as generalists or specialists depending on the taxonomic relatedness of the plants they use as food or oviposition substrates. The plasticity in host plant selection behavior of species belonging to the two categories received little attention. In the present work, fifth instar caterpillars of the generalist herbivore Helicoverpa armigera and its closely related species, the specialist Helicoverpa assulta, were fed on common host plants or artificial diet, after which their feeding preference was assessed individually by using dual - and triple- plant choice assays. Results show both the two Helicoverpa species have a preference hierarchy for host plants. Compared to the fixed preference hierarchy of the specialist H. assulta, the generalist H. armigera exhibited extensive plasticity in feeding preference depending on the host plant experienced during larval development. Whereas the specialist H. assulta exhibited a rigid preference in both dual and triple-plant choice assays, our findings demonstrate that the generalist H. armigera expressed stronger preferences in the dual-plant choice assay than in the triple-plant choice assay. Our results provide additional evidence supporting the neural constraints hypothesis which predicts that generalist herbivores make less accurate decisions than specialists when selecting plants.